Evaluating multi-state systems reliability with a new improved method - Yasser Lamalem; Soufiane Hamida; Yassine Tazouti; Oussama El Gannour; Khalid Housni; Bouchaib Cherradi (Bulletin of Electrical Engineering and Informatics, 2022)
The computation of network reliability for a system with many states is an NP-hard issue. Finding all the minimum path vectors (d-MPs) lower boundary points for each level d is one of the few approaches for computing such dependability. This research proposed enhancements to the technique described in Chen's "Searching for d-MPs with rapid enumeration" paper. We propose additional adjustments to the method that creates the flow vector F in this enhancement. This decreases the number of required steps and the temporal complexity of the method. Comparing the newly suggested approach to the old algorithm reveals that the adjustment has increased the enumeration's efficiency and degree of complexity.